The Roles of Additive Effect between Swine Keeping Systems and Agro-Ecological Zones in Production and Socioeconomic Traits - D. A. Iyai; M. Sagrim; S. Pakage; A. G. Murwanto (Jurnal Sain Peternakan Indonesia, 2020)
The aim of this research was to characterize swine farming system performances tethered under different agro-ecological zones in Papua. The field study was done in Manokwari regency and involved six districts, i.e. Nothern Manokwari district, Eastern Manokari District, Western Manokwari district, Warmare district, Prafi district and Masni district. Respondents chosen were guided by local extensions, originated from 15 villages. Participatory situation analysis (PSA) was employed to approach swine farmers by using questionnaire. Swine body weights of swinelets and growers were weighed except for mature swine, body lengths and hearth girths were measured using tape. Herd number, number of swinelets, adult swine were recorded. A one-way analysis of variances was used. All data were entered in Excel and analyzed using SPPS version 10.0.. The findings shown that interaction between education and keeping systems occur on work hours and ages. Effect of education is significant on experience, location, and ethnic. In keeping systems, effect is real on experience, work hours, location, and ethnic. Interaction do not significant exist in number of swine including see middle man, visited consumer, litter size, number of farrowing and income sources.